2020
DOI: 10.1111/ene.14337
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific association of urate and levodopa‐induced dyskinesia in Parkinson’s disease

Abstract: Background and purpose As a major antioxidant, uric acid (UA) is known to be associated with the clinical progression of Parkinson’s disease (PD). This study investigated whether baseline UA levels are associated with the risk for levodopa‐induced dyskinesia (LID) in PD in a sex‐dependent manner. Methods In all, 152 patients with de novo PD (78 males and 74 females) who were followed up for >2 years were enrolled. The effect of baseline serum UA levels on LID‐free survival was assessed by Cox regression, separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…34,35 In this sense, a previous study has not observed either relation of the risk of LID and UA levels in PD women. 11 Despite the literature, the results presented here suggest a relation between low UA levels and dyskinesia in PD women. In line with our results, an epidemiological cohort study suggested a slight inverse association between UA levels and the risk of DP in the female sex, but less significantly than in men 36 or only being observed after 8 years of follow-up.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…34,35 In this sense, a previous study has not observed either relation of the risk of LID and UA levels in PD women. 11 Despite the literature, the results presented here suggest a relation between low UA levels and dyskinesia in PD women. In line with our results, an epidemiological cohort study suggested a slight inverse association between UA levels and the risk of DP in the female sex, but less significantly than in men 36 or only being observed after 8 years of follow-up.…”
Section: Discussioncontrasting
confidence: 68%
“…However, a recent study that investigated the role of UA on LID in PD patients found an oppositive result, showing that higher serum UA levels are associated with increased risk of LID in men with PD. 11 Given the evidence about the relation of nigrostriatal depletion with UA and, with the appearance of LIDs, we hypothesize that lower serum UA levels are related with the presence of LID in PD patients. Additionally, we explored for possible associations among serum UA levels and clinical features of PD.…”
Section: ► Doença Dementioning
confidence: 88%
See 2 more Smart Citations
“…Hyperuricemia can lead to complications such as heart failure, high blood pressure, kidney failure and diabetes mellitus [ 11 ]. In addition, several drugs used to treat other comorbidities can increase serum uric acid levels, such as diuretics, especially thiazides [ 12 ], immunosuppressants such as Ciclosporin [ 3 ], cytotoxic chemotherapy [ 13 ], and Levodopa [ 14 ], among other pharmaceutical formulations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%